Environmental impact of Bitumen on soil, water and plant in Lodasa Area, Ode-Irele, Ondo state, Nigeria (Journal of Science and Technology, 2016)
Six sites containing various plants with different indicator parts were analyzed for the environmental effects of bitumen on the plants and animals. From the location, which is in Lodasa, Ode-Irele LocalGovernment Area of Ondo State, twelve soil samples, six plant and water samples were collected to study the effects of bitumen on them. Results show that the percentage composition of nitrogen in theplants ranged from 0.069-0.078, for phosphorous it ranged from 0.031-0.068, potassium from 0.16- 0.23, calcium ranged from 0.212-0.288, for magnesium, 0.104-0.188. Constituents of Manganese ranges from 17.07-21.03 ppm, Zinc 13.25-16.20 ppm, Copper, 1.93-2.33 ppm and Iron ranges from 31.25-36.24 ppm all in plants analyzed. As for the composition of these constituents in soils, Nitrogen ranges from 1.058-3.61 ppm, Calcium, 0.66 – 0.88 ppm, Magnesium, 0.65-0.88 and organic matter ranges from 1.788-2.142 ppm. Evidently these show that the soils cannot support plant growthand their effects were manifested in visual signs of dying plants in the bitumen affected areas. The results for water samples have values below the standard recommended by the World Health organization(WHO) for safe drinking water while calcium and manganese values are above the WHO Standard. As for the results of waters samples analyzed, Manganese ranges from 1.63-2.94 ppm, Calcium,3.22- 8.63 ppm, Iron 0.28-0.43ppm, Copper 0.19-0.38ppm while Magnesium ranges from 2.85- 4.77 ppm. These show that the water was toxic and injurious to human, animals and aquatic lives.Statistical analysis shows a positive linear correlation between the presence of nutrients in plants and the soil, which is responsible for the retarded growth and yellow colouration of the leaves. The presenceof bitumen in Lodasa soil is fast eroding soil fertility in the area and has contributed immensely to low yield of Agricultural products. The use of organic fertilizer to boost soil fertility, relocation and resettlement of farmers to areas with high soil fertility and appropriate legislation to protect the rights of the native settlers are some of the recommendations.